Targeting Activated Synovial Fibroblasts in Rheumatoid Arthritis by Peficitinib - Diller, Magnus; Hasseli, Rebecca; Hülser, Marie-Lisa; Aykara, Iris; Frommer, Klaus; Rehart, Stefan; Müller-Ladner, Ulf; Neumann, Elena; Justus Liebig University Giessen (My University, 2019)
Background: Synovial fibroblasts (SF) play a major role in the pathogenesis of rheumatoid arthritis (RA) and develop an aggressive phenotype destroying cartilage and bone, thus termed RASF. JAK inhibitors have shown to be an efficient therapeutic option in RA treatment, but less is known about the effect of JAK inhibitors on activated RASF. The aim of the study was to examine the effects of JAK inhibitors on activated RASF.Methods: Synovium of RA patients was obtained during knee replacement surgeries. Synoviocytes were isolated and pretreated with JAK inhibitors. Pro-inflammatory cytokines and matrix degrading proteinases were measured by ELISA in supernatant after stimulation with oncostatin M or IL-1beta. The proliferation of RASF was measured by BrdU incorporation. Cell culture inserts were used to evaluate cell migration. For adhesion assays, RASF were seeded in culture plates. Then, plates were extensively shaken and adherent RASF quantified. Cell viability, cytotoxicity and apoptosis were measured using the ApoTox-Glo Triplex and the CellTox Green Cytotoxicity Assay.Results: Tofacitinib and baricitinib decreased the IL-6 release of RASF stimulated with oncostatin M. JAK inhibition attenuated the IL-6 release of IL-1beta activated and with soluble IL-6 receptor treated RASF. In contrast, only peficitinib and filgotinib decreased the IL-6 release of RASF activated with IL-1beta. Peficitinib decreased also the MMP-3, CXCL8, and CXCL1 release at 5 muM. Moreover, peficitinib was the only JAK inhibitor suppressing proliferation of activated RASF at 1 muM. Peficitinib further decreased the migration of RASF without being cytotoxic or pro-apoptotic and without altering cell adhesion.Conclusions: JAK inhibitors effectively suppress the inflammatory response induced by oncostatin M and by transsignaling of IL-6 in RASF. Only peficitinib modulated the IL-1beta-induced response of RASF and their proliferation in vitro at concentrations close to reported Cmax values of well tolerated doses in vivo. In contrast to filgotinib, peficitinib also highly suppressed RASF migration showing the potential of peficitinib to target RASF.
Keywords: JAK inhibition; peficitinib; synovial fibroblast; rheumatoid arthritis; IL-1beta; ddc:610